Haemaphysalis longicornis Neumann 1901 ... - Heath, Allen C. G.; Palma, Ricardo L.; Cane, Rachel P.; Hardwick, Scott (Zenodo, 2011)
Haemaphysalis longicornis Neumann, 1901 Host(s) Land birds: Apteryx mantelli, Gallus gallus gallus, Phasianus colchicus, Meleagris gallopavo, Anas platyrhynchos platyrhynchos, Circus approximans, Gallirallus philippensis assimilis, Gallirallus australis greyi, Alauda arvensis, Turdus philomelos, Acridotheres tristis, Passer domesticus, Emberiza citrinella. Mammals: Capra hircus, Bos taurus, Ovis aries, Canis familiaris, Dama dama, Cervus elaphus, Cervus timorensis, Cervus unicolor, Equus asinus, Equus caballus, Erinaceus europaeus, Felis catus, Lepus europaeus, Oryctolagus cuniculus, Rattus rattus, Rattus norvegicus, Mus musculus, Mustela furo, Mustela nivalis, Mustela erminea, Sus scrofa, Trichosurus vulpecula, Homo sapiens. Distribution World: Japan, China, former USSR, Korea, Australia (south-eastern Queensland, coastal New South Wales and Victoria; localised population in Western Australia), New Caledonia, Fiji, Western Samoa, Tonga, Vanuatu; (not established in Hawaii, contra Cane 2011, last updated ... : Published as part of Heath, Allen C. G., Palma, Ricardo L., Cane, Rachel P. & Hardwick, Scott, 2011, Checklist of New Zealand ticks (Acari: Ixodidae, Argasidae), pp. 55-63 in Zootaxa 2995 on page 58, DOI: 10.5281/zenodo.203775 ...